Kewenangan Menteri Keuangan Dalam Pemilihan Ketua Dan Wakil Ketua Pengadilan Pajak Setelah Dikeluarkannya Putusan Mahkamah Konstitusi Nomor 10/PUU-XVIII/2020 - Rizkityas Sekar Handini; Budi Ispriyarso; Nabitatus Sa’adah (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2022)
Abstract:This research aims to describe the authority of the Minister of Finance regarding the mechanism for selecting the Chair and Deputy Chairperson of the Tax Court and the realization of an independent Tax Court after the decision of the Constitutional Court Number 10/PUU-XVIII/2020. This research is a qualitative research using a normative approach. The results of this study state that the authority of the Minister of Finance in the election of the Chair and Deputy Chairperson of the Tax Court is only administrative in following up the results of the election of the Chair and Deputy Chairmen submitted to the President after obtaining approval from the Chief Justice of the Supreme Court and the decision of the Constitutional Court in changing the mechanism for selecting the Chairperson. and the Deputy Chairperson of the Tax Court can encourage the realization of the independence of the Tax Court. Independence in the Tax Court needs to be given attention considering that there are still several weaknesses that make the Tax Court not yet fully independent. Keywords: Authority; Tax Court; Independence; Constitutional Court Decision Abstrak: Penelitian ini bertujuan untuk mendeskripsikan kewenangan Menteri Keuangan terkait mekanisme pemilihan Ketua dan Wakil Ketua Pengadilan Pajak dan perwujudan Pengadilan Pajak yang independen setelah adanya putusan Mahkamah Konstitusi Nomor 10/PUU-XVIII/2020. Penelitian ini merupakan penelitian kualitatif dengan menggunakan metode pendekatan normatif. Hasil dari penelitian ini menyatakan bahwa kewenangan Menteri Keuangan dalam pemilihan Ketua dan Wakil Ketua Pengadilan Pajak hanya bersifat administratif dalam menindaklanjuti hasil dari pemilihan Ketua dan Wakil Ketua yang diajukan kepada Presiden setelah mendapat persetujuan Ketua Mahkamah Agung dan adanya putusan Mahkamah Konstitusi tersebut dalam perubahan mekanisme pemilihan Ketua dan Wakil Ketua Pengadilan Pajak dapat mendorong perwujudan independensi Pengadilan Pajak. Independensi dalam Pengadilan Pajak perlu diberi perhatian mengingat masih terdapat beberapa kelemahan yang menjadikan Pengadilan Pajak belum sepenuhnya Independen. Kata Kunci: Kewenangan; Pengadilan Pajak; Independensi; Putusan Mahkamah Konstitusi